2020
DOI: 10.1016/j.jmoneco.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The economic effects of trade policy uncertainty

Abstract: We study the effects of unexpected changes in trade policy uncertainty (T P U ) on the U.S. economy. We construct three measures of T P U based on newspaper coverage, firms' earnings conference calls, and aggregate data on tariff rates. We document that increases in T P U reduce investment and activity using both firm-level and aggregate macroeconomic data. We interpret the empirical results through the lens of a two-country general equilibrium model with nominal rigidities and firms' export participation deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
165
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(207 citation statements)
references
References 42 publications
5
165
0
Order By: Relevance
“…aggregate price index are only somewhat stronger than under endogenous domestic entry (because the absence of a domestic extensive margin is partially offset by a larger intensive margin impact). 39 The US firms respond to the general equilibrium price index changes, as they did in the two-country model, but so do any other non-Chinese firms that face constant trade barriers in the United States. It is simple to show that, because we are solving for changes, this is the outcome from extending the model to multiple countries as long as all non-Chinese firms face a common σ and k , as is typical in this type of model, and a similar expectation of the duration of the low protection state, u h .…”
Section: A Quantification: Exportsmentioning
confidence: 94%
See 1 more Smart Citation
“…aggregate price index are only somewhat stronger than under endogenous domestic entry (because the absence of a domestic extensive margin is partially offset by a larger intensive margin impact). 39 The US firms respond to the general equilibrium price index changes, as they did in the two-country model, but so do any other non-Chinese firms that face constant trade barriers in the United States. It is simple to show that, because we are solving for changes, this is the outcome from extending the model to multiple countries as long as all non-Chinese firms face a common σ and k , as is typical in this type of model, and a similar expectation of the duration of the low protection state, u h .…”
Section: A Quantification: Exportsmentioning
confidence: 94%
“…First, export entry and sales reflect the response of Chinese varieties whereas the domestic entry and sales reflect both US and other non-Chinese varieties. 39 Second, we now account for variation in policy across industries. The main quantitative difference is that in Section IIID we did not have the uncertainty parameters and so described a range of TPU impacts.…”
Section: A Quantification: Exportsmentioning
confidence: 99%
“…While prior studies have shown that uncertainty has far-reaching consequences on firm policies of first order importance (such as investments and hiring), this work has been hampered by the lack of "sound, flexible measures of uncertainty" (Altig et al, 2019). Our work highlights the versatility of text-based measures of uncertainty, adding to recent work which pioneered these approaches in the context of political uncertainty (Baker et al, 2016;Hassan et al, 2019) and applied them to themes like trade policy (Handley and Li, 2018;Caldara et al, 2019;Kost, 2019).…”
mentioning
confidence: 89%
“…Committee on Finance, 2018). Caldara, Iacoviello, Molligo, Prestipino and Raffo (2019) find that when firms discussed tariffs and policy uncertainty on earnings calls in recent years, the primary concern cited was their supply chains. Another example is documented in the Federal Reserve Beige Book (November 27, 2019) " [...] firms have reported tariff impacts on sales, either in terms of pricing or in terms of supply chain disruptions slowing their product supply.…”
Section: Introductionmentioning
confidence: 99%